1998
DOI: 10.1063/1.122521
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tunneling in p+ amorphous silicon carbide n crystalline silicon heterojunction solar cells

Abstract: We used the internal photoemission (IPE) technique to accurately determine the valence and conduction band offsets at the a-SiC:H/c-Si interface and investigated with numerical simulations their effects on the photocarrier collection in p+ a-SiC:H/n c-Si heterojunction solar cells. The valence and conduction band discontinuities were found to be 0.60 and 0.55 eV, respectively. However, despite the large barrier at the valence band edge, 30 nm p+ a-SiC:H/n c-Si heterojunction solar cells show no collection prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…3 imply that another transport path becomes prevalent once ∆E V is increasing well above the thermal energy of carriers at 300 K. Indeed, there are a few simulation studies which ascribe a significant importance to tunneling through the interface 12,14 or tunnel hopping in valence band tail states 13,38 in the a-Si:H layers.…”
Section: 35-37mentioning
confidence: 99%
See 1 more Smart Citation
“…3 imply that another transport path becomes prevalent once ∆E V is increasing well above the thermal energy of carriers at 300 K. Indeed, there are a few simulation studies which ascribe a significant importance to tunneling through the interface 12,14 or tunnel hopping in valence band tail states 13,38 in the a-Si:H layers.…”
Section: 35-37mentioning
confidence: 99%
“…An increase of ∆E V at the hole contact leads to the development of sshaped j(U) curves. This behavior was predicted on the basis of numerical simulations, 4,12,13 but no systematic experimental evidence has been presented so far. The V OC of the solar cells decreases slowly for increasing ∆E V .…”
mentioning
confidence: 99%
“…Modeling of HIT structures on N-type c-Si substrate has already been carried out by a few groups, [12][13][14]16 one of which 12 has tried to establish that tunneling of holes across the potential barrier due to the large valence band discontinuity, which may explain the high FF in these structures. The second group, 13,14 however, has ignored tunneling and has shown that the HIT cells on N-type c-Si substrates are expected to have higher values of both J sc and V oc , but lower values of the FF, relative to HIT cells on P-type c-Si substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Computer modeling of HIT structures has been carried out, not only to understand carrier transport in these structures, [12][13][14][15][16] but also to assess which HIT structure-whether on N-type or P-type c-Si substrate-is capable of attaining the higher efficiency. 13,14,17 In this article, we have used the detailed numerical electrical-optical model, Amorphous Semiconductor Device Modeling Program ͑ASDMP͒, 18,19 to trace the development of the Sanyo cells, beginning with their initial front HIT ͑with a heterojunction ͑HJ͒ only on the emitter side, and a conventional BSF layer, that is part of the c-Si wafer itself͒ solar cells, having rather low values of the open-circuit voltages ͑V oc ͒.…”
Section: Introductionmentioning
confidence: 99%
“…͓DOI: 10.1063/1.3132053͔ P type amorphous Si x C 1−x ͑a-SiC͒ and nanocrystalline silicon-carbide ͑nc-SiC͒ films have attracted considerable research interest as a material for constructing high efficiency silicon solar cells. [1][2][3][4] Compared to a-SiC, nc-SiC has higher electrical conductivity, which can significantly improve the solar cell efficiency. [4][5][6] To date, a number of methods have been developed to crystallize deposited amorphous SiC layer, including ion-beam induced crystallization, 7,8 alternating aluminum layer induced crystallization, 9,10 and laser induced crystallization.…”
mentioning
confidence: 99%